How do Non-Monetary Performance Incentives for Physicians Affect the Quality of Medical Care? – A Laboratory Experiment - Nadja Kairies; Miriam Krieger (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
In recent years, several countries have introduced non-monetary performance incentives for health care providers to improve the quality of medical care. Evidence on the effect of non-monetary feedback incentives, predominantly in the form of public quality reporting, on the quality of medical care is, however, ambiguous. This is often because empirical research to date has not succeeded in distinguishing between the effects of monetary and non-monetary incentives, which are usually implemented simultaneously. We use a controlled laboratory experiment to isolate the impact of nonmonetary performance incentives: subjects take on the role of physicians and make treatment decisions for patients, receiving feedback on the quality of their treatment. The subjects' decisions result in payments to real patients. By giving either private or public feedback we are able to disentangle the motivational effects of self-esteem and social reputation. Our results reveal that public feedback incentives have a significant and positive effect on the quality of care that is provided. Private feedback, on the other hand, has no impact on treatment quality. These results hold for medical students and for other students. – – In den vergangenen Jahren wurden in mehreren Ländern nicht-monetäre Leistungsanreize für Anbieter medizinischer Leistungen eingeführt, um die medizinische Versorgungsqualität zu verbessern. Die Wirkung nicht-monetärer Feedback-Anreize, vorwiegend in Form von öffentlichen Qualitätsberichten implementiert, ist jedoch nicht eindeutig belegt. Dies ist häufig darauf zurückzuführen, dass es in empirischen Studien bisher nicht gelang, die Effekte monetärer und nicht-monetärer Anreizen - in der Praxis meist gemeinsam implementiert - voneinander zu trennen. Wir führen ein kontrolliertes Laborexperiment durch, um den Einfluss von nicht-monetären Leitungsanreizen zu isolieren: Teilnehmer nehmen die Rolle eines Arztes ein und treffen Behandlungsentscheidungen für Patienten, wobei sie Feedback über die Qualität ihrer Behandlung erhalten. Die Entscheidungen der Teilnehmer führen zu Zahlungen an reale Patienten. Indem wir entweder privates oder öffentliches Feedback geben, können wir die Motivationseffekte von Selbstwertgefühl und sozialer Reputation voneinander trennen. Unsere Ergebnisse zeigen, dass öffentliche Feedback-Anreize einen signifikant positiven Effekt auf die bereitgestellte Behandlungsqualität haben. Privates Feedback hingegen hat keinen Einfluss auf die Behandlungsqualität. Diese Resultate gelten für Medizinstudenten sowie andere Studenten.
Keywords: I11; C91; L15; I18; 330; laboratory experiment; quality reporting; feedback; treatment quality; performance incentives